Pedagogical and Curricular Needs for ISTEAM Learning in Islamic Early Childhood Education at PAUD Kiddos English School Banda Aceh - Nuraida, Nuraida; Amelia, Lina; Miharti, Ridha; Andriansyah, Andriansyah; Kamaliah, Nurul (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study examines the pedagogical and curricular needs for ISTEAM (Islamic Science, Technology, Engineering, Arts, and Mathematics) learning in Islamic early childhood education at PAUD Kiddos English School Banda Aceh. Rather than claiming to develop or validate a full ISTEAM model, the study positions ISTEAM as a sensitizing framework for understanding how Islamic values, STEAM activities, lesson planning, and assessment are currently connected in one institutional context.Design/methods/approach – A qualitative case study design was employed. Data were collected through semi-structured interviews with the principal and five classroom teachers, six non-participant classroom observations, and a structured needs questionnaire used as descriptive triangulation. Interview and observation data were analyzed using six-phase thematic analysis (Braun & Clarke, 2006), while questionnaire responses were used to support the interpretation of recurring needs without statistical generalization.Findings – Three themes emerged. First, PAUD Kiddos has an institutional culture supportive of ISTEAM, with Islamic routines and STEAM-related activities already present in daily practice. Second, there is a gap between verbal or intuitive integration and formal curricular documentation: two of six teachers had documented Islamic value integration in lesson plans, and none had written explicit Qur'anic or hadith connections into learning objectives. Third, the most visible needs were an ISTEAM lesson-plan template, a contextual Qur'an/hadith reference bank, hands-on teacher workshops, integrated assessment rubrics, and formal school-level policy support.Research implications/limitations – The findings should be interpreted as context-bound evidence from one Islamic early childhood institution with six adult participants and six observed classroom sessions. Future research should develop, pilot, and validate ISTEAM learning tools across more diverse Islamic PAUD settings.Practical implications – The findings provide actionable guidance for Islamic early childhood education providers, teacher educators, and curriculum developers in designing contextually appropriate ISTEAM implementation. The identified needs can inform the development of lesson-plan templates, teacher professional development programs, curriculum guidelines, and assessment instruments that systematically integrate Islamic values with STEAM learning in early childhood classrooms.Originality/value – The article contributes a local, practice-oriented needs map for ISTEAM learning in Islamic early childhood education. Its contribution is not a finalized model, but an empirically grounded preliminary basis for subsequent design-based development of ISTEAM lesson planning, classroom activities, and assessment tools.Paper type Research paper